Indentation effect on the fatigue limit of axle steel - GAO Jie-wei; DAI Guang-ze; ZHAO Jun-wen; LI Heng-kui; XU Lei (工程科学学报)
A hardness tester was used to make indentations on the hourglass fatigue specimens of axle steel,and notches were machined by electronic discharge machining(EDM).The fatigue limits of both indentation specimens and notched ones were examined and compared with the theoretical values according to the Murakami formula based on material hardness and defect projected area.The fracture surface was observed by scanning electron microscopy.It is found that local work hardening and residual stress caused by plastic deformation of indentations have no significant effect on the fatigue limits in comparison with the predicted values by the Murakami equation.Fatigue cracks originate from the bottom of indentations due to stress concentration effect.The fatigue limits of notched specimens are lower than the calculated values because of secondary notches caused by the high roughness of notch surfaces and the existence of microcracks and micropores within the re-cast layers.Cracks initiate from multiple sites on the bottom of electronic discharge machining notches.